Biochemical characterisation of putrescine and spermidine uptake as a potential therapeutic target against the human malaria parasite, Plasmodium falciparum - Birkholtz, Lyn-Marie (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2012.